A descriptive study of tobacco use in adults in an urban slum - Koshy, George; Gangadharan, Vandana; Koshy, Varghese (International Journal Of Community Medicine And Public Health, 2017)
Background: Globally, nearly 5 million persons die every year from tobacco-related illnesses, with disproporti-onately higher mortality occurring in developing countries. Tobacco is used in a multitude of ways in India. By 2020 India would have the highest rate of rise in tobacco related deaths compared to all other countries. Tobacco use in India is increasing but there are considerable changes in the types and methods by which it is used. According to WHO estimates, 194 million men and 45 million women use tobacco in smoked or smokeless form in India. Tobacco use is the leading preventable cause of death in developed countries and is the second leading cause of death globally. The study was carried out to assess the practice of tobacco use among adults in urban slum. It tries to ascertain the prevalence of tobacco use in the community, identify the various forms of tobacco used. It is a questionnaire based cross sectional descriptive study. Methods: A cross sectional descriptive study using a close-ended, pre tested structured interview schedule was prepared and the investigator conducted the interviews personally at the respondent’s house who were above 18 years of age. Results: The prevalence of tobacco use in any form was found to be 38.78%, the most common age group being 30-44 yrs. Also seeing that initiation of tobacco use took place in the age group 20-29 yrs it highlights the need of starting anti-tobacco campaigns for a younger age group but not leaving out older age groups at the same time. Sex-wise distribution of tobacco use was observed to be 40.23% in males as compared to 36.17% in females. Conclusions: Control of this deadly epidemic requires a decisive, target oriented and a well motivated approach.